PENGARUH CITRA MEREK, KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI MINUMAN ISOTONIK MEREK MIZONE DI KOTA SEMARANG (Students' Journal of Economic and Management, 2015)
Buying interest is the tendency of consumers to buy a brand or take action relating to the purchase of which is measured by the degree of likelihood that consumers make purchases. Basically interest is an attitude that can make a person feel happy to objects or situations or certain ideas which are usually followed by a sense of excitement and a tendency to look for the favored object. A person of interest in both permanent or temporary, and the various systems of the dominant motivation is internal determinants that truly fundamental in influencing his attention. Consumer interest can be affected by many factors, such as brand image, product quality and price. The purpose of this study was to analyze the influence of brand image, product quality and price on the buying interest. The population in this study is the consumer brand of isotonic drinks Mizone in Semarang City. The sample in this study was 100 consumers. The sampling technique used purposive sampling (sampling with the goal). The type of data and data collection techniques used are primary. The analysis technique used is descriptive analysis and multiple linear regression analysis. The results showed that: (1). Brand image affect on buying interest. (2). Product quality affect on buying interest. (3). Price affect on buying interest.Keyword :  Brand Image, Quality Products, Price, Buying Interes